A cyclic AMP-activated K+ channel in Drosophila larval muscle is persistently activated in dunce. - Delgado, R (1991)
Single-channel recording from longitudinal ventrolateral Drosophila larval muscle reveals the presence of a potassium-selective channel that is directly and reversibly activated by cAMP in a dose-dependent fashion. Activation is specific and it cannot be mimicked by a series of agents that include AMP, cGMP, ATP, inositol trisphosphate, and Ca2+. Channel current records obtained from larval muscle in different dunce mutants possessing abnormally high levels of cAMP show that, in the mutants, the channel displays an increased probability of opening.